Pancasila As A Development Paradigm - Muhammad Yogi Triyadi; Widia Anggelina; masduki asbari (Journal of Information Systems and Management (JISMA), 2022)
This paper is to formulate a conceptual perspective on the reconstruction of the paradigm of the development of the rule of law in Indonesia. Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia states that "the Indonesian state is a state of law", but in reality it is a sector that is worse off than other sectors. This downturn can be interpreted as the absence of a clear paradigmatic foundation on how state law is to be built and developed. The reconstruction of the paradigm of the development of the Indonesian legal state starts from the existence of Pancasila as the philosophy of the Indonesian nation.